Discurso bíblico: O funcionamento da autoria e a ressignificação de sentidos no Evangelho segundo Mateus - Silva, Aline Eloisa da (2022)
Biblical texts are among the oldest writings circulating in Western civilization. Through them, it was possible to have access to the culture of a people and have a basis for the development of knowledge related to Art, Literature, Geography, Archeology and History. In the area of Linguistics, we found a favorable field for working with them, since the possibilities of analysis are many: from the semiotic, semantic and discursive point of view, however, although there is a lot of research related to religious discourse, there are not many works in this field. Discourse Analysis that address the biblical text. Bringing DA into the study of these texts is not only relevant for those who have religion as a field of study, as it can also contribute to the renewal of exegetical studies. Since every text is subject to analysis, and that, faced with a text, the subject is urged to signify it, we will seek through the narrative of the Sermon on the Mount, present in the New Testament, of the Gospel according to Matthew to understand how the functioning of the authorship produces a movement of speech reproduction at the same time that it allows the re-signification of its meanings.In this context, the analysis allows us to understand how the first and second testaments are interconnected and that makes the resignification of meanings possible through Matthew's rereading of the Mosaic law. Keywords: Discourse Analysis; Biblical Text; Authorship; Resignification of meanings.